Infrared stealth hybrid Mxene aerogel, preparation method and application

By doping modified nanomaterials in MXene aerogel, the problems of weak gelation ability and easy overlap in structure are solved, and the high mechanical strength and good infrared stealth performance of the aerogel are achieved, improving the far-infrared extinction performance and comprehensive infrared stealth effect.

CN119746737APending Publication Date: 2025-04-04JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411950555.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

As a stealth material, MXene has the problem of weak gelation ability and easy overlap in structure, which makes it difficult for it to form aerogels with good mechanical properties and continuous porous structures, which in turn affects its infrared stealth performance.

Method used

By doping modified silicon carbide nanowires, modified carbon nanotubes and modified reduced graphene oxide, the gelation ability and structural stability of MXene are improved, and the mechanical strength and heat dissipation performance of the aerogel are improved, thereby improving its infrared stealth performance.

Benefits of technology

The low density and low infrared emissivity characteristics of the aerogel are achieved, the medium and far infrared extinction performance and comprehensive infrared stealth performance are improved, and the infrared stealth effect of the MXene aerogel is significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of stealth, and provides an infrared stealth hybrid Mxene aerogel, a preparation method and application, and the infrared stealth hybrid Mxene aerogel is the infrared stealth hybrid Mxene aerogel doped with modified silicon carbide nanowires (SiCnw), modified carbon nanotubes (CNTs) and modified reduced graphene oxide (RGO). The MXene aerogel is used as a main body, and the infrared radiation difference between an aerogel smoke screen and the surrounding environment can be reduced by utilizing the low infrared emission characteristic of the MXene material; by adding the modified RGO, the middle and far infrared extinction performance of the aerogel smoke screen is improved; by introducing CNTs as a cross-linking agent, combination of RGO and MXene is realized, and the weak gelation phenomenon of MXene is improved; the mechanical strength of the MXene aerogel is improved by introducing modified SiCnw, and uniform smoke screen heat dissipation is realized by utilizing the characteristic of high heat conductivity of the MXene aerogel. The infrared stealth hybrid MXene aerogel material has good infrared delustering performance and is suitable for being used as an infrared delustering agent in a stealth smoke screen material, and infrared stealth is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of infrared stealth technology, and in particular to an infrared stealth hybrid Mxene aerogel for stealth smoke screen, a preparation method and an application thereof. Background Art

[0002] In recent years, with the rapid development of infrared detection technology, the development of infrared stealth materials has become an urgent need to achieve target stealth. Among them, aerogel, as a highly porous material with a 3D interpenetrating network, has extremely low density, low thermal conductivity and high specific surface area, and has gradually become an emerging infrared stealth material. The selection of aerogel synthetic materials is the key to achieving infrared stealth. There is an urgent need for an infrared stealth aerogel material with both low density and low emissivity to achieve infrared stealth of the target.

[0003] New two-dimensional material MXene (Ti 3 C 2 T x ) refers to transition metal carbon / nitrogen / carbonitride (such as Ti 3 C 2 ) derived two-dimensional layered materials, specifically a class of materials with M n+1 X n T x The material system composed of elements has the characteristics of low thermal conductivity, low density, high porosity, large specific surface area, porous network structure, adjustable structure, etc., and has low emissivity characteristics in the low infrared region. Using it as an aerogel material can achieve target invisibility in the low infrared emission area. However, MXene itself has weak gelation ability and tends to overlap, making it difficult to spontaneously form an aerogel with good mechanical properties and a continuous porous structure.

[0004] Graphene oxide is the product of graphite powder after chemical oxidation and exfoliation. It has certain extinction properties in the mid- and far-infrared, and can be combined with Mxene to improve the comprehensive infrared stealth performance. Since graphene oxide particles are easy to agglomerate when mixed with other substances, which affects the dispersion effect, they often need to be modified.

[0005] Carbon nanotubes are nanoscale fibrous materials composed of carbon elements, which are widely used in energy storage, high-performance composite materials and other fields. CNTs have a unique high specific surface area and mechanical strength, and are suitable for a variety of application scenarios due to their structural adjustability.

[0006] SiC nanowire is a single crystal fiber with a radial dimension less than 100nm and a length dimension much larger than the radial dimension. It has been widely used in aerospace, automotive machinery, chemical industry, electronics and other industrial fields due to its excellent thermal conductivity and high mechanical strength. It can be used in aerogel materials to improve the mechanical strength of aerogel and achieve uniform heat dissipation of gel. Summary of the invention

[0007] In view of the problems existing in MXene as a stealth material, the present invention provides an infrared stealth hybrid MXene aerogel for stealth smoke screen and a preparation method thereof, which improves the mechanical strength of the gel, improves the weak gelation phenomenon of MXene, realizes uniform heat dissipation of the gel, improves the mid-infrared and far-infrared extinction performance of the aerogel smoke screen, and improves the comprehensive infrared stealth performance of the aerogel by doping modified silicon carbide nanowires, modified carbon nanotubes and modified reduced graphene oxide. The hybrid MXene aerogel has the characteristics of extremely low density and low infrared emissivity. On the other hand, the present invention also provides the application of the hybrid MXene aerogel.

[0008] The present invention achieves the above technical objectives through the following technical means.

[0009] A method for preparing infrared stealth hybrid Mxene aerogel, characterized in that it comprises the following steps:

[0010] (1) Preparation of TI 3 C 2 T X Mxene solution, modified silicon carbide nanowire (SiCnw) powder, modified GO solution, and modified carbon nanotubes (CNTs) were ultrasonically mixed and then added to TI 3 C 2 T X The Mxene solution was heated in a water bath under an argon atmosphere and stirred to mix, and then I-ascorbic acid (VC) was added and continued to stir, and then cooled in an ice bath to obtain a hybrid Mxene hydrosol;

[0011] The modified silicon carbide nanowire (SiCnw) is a positively charged SiCnw modified by cations;

[0012] The modified reduced graphene oxide (RGO) is PA-GO modified graphene oxide modified by phthalic anhydride (PA) and having carboxyl groups on the surface;

[0013] The modified CNTs are modified carbon nanotubes with hydroxyl groups on the surface;

[0014] (2) performing solvent replacement on the hybrid Mxene hydrosol and freeze-drying to obtain a hybrid Mxene aerogel;

[0015] (3) Annealing the aerogel at 600-610 °C under argon conditions to obtain the desired infrared stealth hybrid MXene aerogel.

[0016] Furthermore, in the step (1), the mass ratio of MXene solution, modified SiCnw powder, modified GO solution, modified CNTs, and VC is 1: 0.3-0.5: 2-2.3: 0.6-0.8: 0.2-0.4, preferably 1: 0.4-0.5: 2.2-2.3: 0.7-0.8: 0.3-0.4.

[0017] Furthermore, the TI 3 C 2 T X The preparation method of Mxene solution is as follows: 3 ALC 2 Add to the hydrochloric acid solution containing LIF and stir to mix; after the reaction is complete, collect the precipitate by centrifugation; add hydrochloric acid to the precipitate, remove the excess unreacted LIF by centrifugation; rinse with deionized water until the pH reaches 6.5-7.5, collect the precipitate by centrifugation; add deionized water to the precipitate, treat with ultrasound in an ice water bath for 2 hours, collect the upper solution by centrifugation, and obtain TI 3 C 2 T X Mxene solution; preferably, by weight, to make TI 3 C 2 T X The raw materials required for Mxene solution are: 3 to 6 parts TI 3 ALC 2 , 60-63 parts of hydrochloric acid solution, 3-7 parts of LIF, 75-79 parts of deionized water; the selected hydrochloric acid concentration is 7-9M, preferably 8-9M.

[0018] Furthermore, the modified GO solution preparation method comprises: mixing GO with N-methylpyrrolidone (NMP) and then mixing with phthalic anhydride for modification, adding an appropriate amount of acetone to remove excess phthalic anhydride, and when a large amount of black flocculent precipitate is generated after standing, filtering to remove impurities, repeatedly washing the product with anhydrous ethanol and then vacuum drying to obtain phthalic anhydride grafted graphene oxide; ultrasonically mixing the modified GO with deionized water to obtain a modified GO solution; preferably, the modified GO solution is prepared by mixing the modified GO with deionized water in parts by weight. The raw materials required for preparing the modified GO solution are: 1-3 parts of GO, 99-103 parts of N-methylpyrrolidone, 29-33 parts of phthalic anhydride, 60-63 parts of acetone, 90-93 parts of deionized water, and 90-94 parts of anhydrous ethanol; preferably, when the phthalic anhydride is just added, the reaction temperature is preferably about 63-65°C, and after the phthalic anhydride is completely melted, the modification reaction temperature is preferably 83-85°C, and the reaction time is preferably 1h.

[0019] Furthermore, the modified SiCnw preparation method is: dispersing SiCnw in an L-lysine solution, stirring and centrifuging, washing with anhydrous ethanol and vacuum drying to obtain modified positively charged SiCnw; preferably, the raw materials required for preparing the modified SiCnw are: 1 to 3 parts of SiCnw, 148 to 152 parts of L-lysine, 200 to 202 parts of deionized water, and 199 to 201 parts of anhydrous ethanol.

[0020] Furthermore, the modified CNTs are prepared by electrochemical oxidation, the steps of which are as follows:

[0021] CNTs are added to deionized water and ultrasonically dispersed. After the CNTs are uniformly dispersed, they are coated on a glassy carbon electrode, and after drying, a uniform CNTs thin layer is formed on the glassy carbon electrode; sodium acetate and boric acid are added to the electrolytic cell to form an electrolyte; then, one end of the working electrode, the counter electrode and the reference electrode are inserted into the electrolyte, and the other end is connected to the electrochemical workstation, and a multi-step voltage program is applied for electrochemical oxidation treatment. After the reaction is completed, the working electrode is taken out, fully washed with deionized water, and then dried in a vacuum drying oven at 58 to 60°C for several hours to ensure that the surface of the CNTs is clean, and finally the modified CNTs powder is obtained by physical stripping; preferably, the raw materials required for making modified CNTs are: 1 to 1.3 parts of CNTs, 10 to 13 parts of sodium acetate, 23 to 28 parts of boric acid, and 103 to 108 deionized water in parts by weight.

[0022] Furthermore, in the preparation of modified CNTs, the multi-step voltage program in the electrochemical oxidation treatment includes: the first step, applying a constant potential of 0.7V to 0.8V for 10 to 13 minutes. The second step: applying a constant potential of 1.0 to 1.1V for 5 to 8 minutes. The third step of voltage treatment: applying a constant potential of 0.5 to 0.6V for 4 to 5 minutes. Preferably, the concentrations of the sodium acetate solution and the boric acid solution are both selected to be 0.05M.

[0023] Furthermore, the water bath heating stirring and mixing in step (1) is specifically as follows: first stirring and mixing in a water bath at 58-60° C. under autogenous pressure for 3-4 hours, and then mixing at 68-70° C. under autogenous pressure for 1-2 hours; preferably, the annealing conditions in step (3) are annealing at 1 atm, 600-610° C. under argon conditions for 55-60 minutes, and then pressing at 5-5.2 MPa pressure for 5-6 minutes to remove VC in the hybrid gel.

[0024] The infrared stealth hybrid MXene aerogel prepared by the preparation method is characterized in that it is an infrared stealth hybrid MXene aerogel doped with modified silicon carbide nanowires (SiCnw), modified carbon nanotubes (CNTs) and modified reduced graphene oxide (RGO).

[0025] The application of the infrared stealth hybrid Mxene aerogel is characterized in that it is used as an infrared stealth smoke screen matting agent to prepare an infrared stealth smoke screen smoke forming agent.

[0026] The present invention is provided by TI 3 C 2 T x TI in Mxene solution 3 C 2 T x Mxene material improves the low infrared emission characteristics of aerogel, which can reduce the infrared radiation difference between aerogel smoke screen and the surrounding environment; by adding modified GO, the mid- and far-infrared extinction performance of aerogel smoke screen is improved, and the agglomeration phenomenon of GO particles when mixed with other substances is reduced by modification; by adding VC as a reducing agent to modify the surface functional groups of MXene, MXene oxidation is hindered, and the modified GO is reduced to modified RGO; by adding modified CNTs as a cross-linking agent, the CNTs with rich hydroxyl groups on the surface after modification are used to help the oxygen-containing functional groups on the surface of MXene to combine with the modified RGO through hydrogen bond interaction, thereby improving the comprehensive infrared stealth performance of aerogel and improving the weak gelation phenomenon of Mxene. The mechanical strength of the gel is improved by introducing modified SiCnw, and the heat dissipation of the gel is uniform. The results of the embodiment show that the infrared stealth aerogel provided by the present invention has a shielding rate of 96% in the near-infrared band, 95% in the short-wavelength infrared band, 92% in the medium-wavelength infrared band, and 89% in the visible light. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0028] The present invention uses MXene solution, modified SiCnw powder, modified GO solution, modified CNTs, and I-ascorbic acid (VC) as raw materials to prepare the infrared stealth hybrid MXene aerogel, wherein the mass ratio of the MXene solution, modified SiCnw powder, modified GO solution, modified CNTs, and VC is 1: 0.3-0.5: 2-2.3: 0.6-0.8: 0.2-0.4, preferably 1: 0.4-0.5: 2.2-2.3: 0.7-0.8: 0.3-0.4. 3 C 2 T X The mass ratio of MXene solution, modified SiCnw powder, modified GO solution, modified CNTs and VC is controlled within the above range, which is beneficial to the gelation of the solution.

[0029] The TI 3 C 2 T XThe preparation method of Mxene solution is as follows: 3 ALC 2 Add to the hydrochloric acid solution containing LIF and stir to mix, react at 20-25°C, the stirring rate is preferably 50-200rpm, more preferably 150-200rpm; the stirring time is preferably 30min-1h, more preferably 45min. After the reaction is complete, collect the precipitate by centrifugation; add hydrochloric acid to the precipitate, centrifuge to remove excess unreacted LIF; rinse with deionized water until the pH reaches 6.5-7.5, collect the precipitate by centrifugation, the centrifugal speed is preferably 13000-15000rpm, and the centrifugal time is preferably 10-15 minutes. Add deionized water to the precipitate, ultrasonically treat in an ice water bath for 2h, and collect the upper solution by centrifugation to obtain TI 3 C 2 T X The frequency of the ice bath ultrasonic treatment is preferably 25 to 30 kHz; the ice bath temperature is preferably -2°C to -1°C, the ultrasonic treatment time is 2 hours, and the ultrasonic power is selected to be 50 to 80W.

[0030] The selected hydrochloric acid concentration is 7 to 9 M, preferably 8 to 9 M. The hydrochloric acid is used to provide acidic conditions in the reaction environment to promote TI 3 ALC 2 The concentration and volume of hydrochloric acid directly affect the TI 3 C 2 T X The quality and yield of Mxene. 3 ALC 2 Reaction to prepare TI 3 C 2 T X Mxene, and plays a key role in the control of the reaction process. Deionized water is used to wash the precipitate and dilute the solution to remove unreacted LIF and hydrochloric acid. The amount of deionized water affects the purity of the precipitate and the final TI 3 C 2 T X The cleanliness of the Mxene solution. 3 ALC 2 The sources of HCl and LIF are not particularly limited, and commercially available products known to those skilled in the art may be used.

[0031] Wherein, the TI is prepared 3 C 2 T X The raw materials of Mxene solution are calculated by weight: 3 to 6 parts of TI 3 ALC 2, 60-63 parts of hydrochloric acid solution, 3-7 parts of LIF, 75-79 parts of deionized water.

[0032] TI 3 ALC 2 The dosage is preferably 3 to 5 parts, more preferably 3 to 4 parts. 3 ALC 2 The weight of the mixture is 3 to 4 parts: the amount of hydrochloric acid solution is 60 to 63 parts, preferably 60 to 62 parts, more preferably 60 to 61 parts; the amount of LIF is 3 to 7 parts, preferably 3 to 6 parts, more preferably 3 to 5 parts; the amount of deionized water is 75 to 79 parts, preferably 75 to 78 parts, more preferably 75 to 77 parts.

[0033] The modified GO solution preparation method is as follows: GO is mixed with N-methylpyrrolidone (NMP) and then mixed with phthalic anhydride (PA) for modification, an appropriate amount of acetone is added to remove excess phthalic anhydride (PA), and when a large amount of black flocculent precipitate is generated after standing, impurities are removed by suction filtration, the product is repeatedly washed with anhydrous ethanol and then vacuum dried to obtain phthalic anhydride (PA) grafted graphene oxide. The modified GO is ultrasonically mixed with deionized water to obtain a modified GO solution. Among them, the raw materials required for making the modified GO solution are calculated by weight: 1 to 3 parts of GO, 99 to 103 parts of N-methylpyrrolidone (NMP), 29 to 33 parts of phthalic anhydride (PA), 60 to 63 parts of acetone, 90 to 93 parts of deionized water, and 90 to 94 parts of anhydrous ethanol.

[0034] In terms of weight, the raw materials for preparing the modified GO solution include 1 to 3 parts of GO, preferably 1 to 2 parts, and more preferably 1 part. In the present invention, the GO is used to graft phthalic anhydride (PA) to achieve its modification. The amount of GO directly affects the quality and yield of the modified GO solution. The present invention has no special limitation on the source of the GO, and commercially available products known to those skilled in the art can be used.

[0035] Based on 1 part by weight of GO, the raw materials for preparing the modified GO solution include 99 to 103 parts of N-methylpyrrolidone (NMP), preferably 100 to 103 parts, and more preferably 100 to 102 parts. In the present invention, the N-methylpyrrolidone is used to blend with GO to promote the modification reaction. The amount of N-methylpyrrolidone directly affects the rate of modification. The present invention has no special limitation on the source of the N-methylpyrrolidone (NMP), and commercially available products well known to those skilled in the art can be used.

[0036] Based on 1 part by weight of GO, the raw materials for preparing the modified GO solution include 29 to 33 parts of phthalic anhydride (PA), preferably 29 to 32 parts, and more preferably 30 to 32 parts. In the present invention, the phthalic anhydride is used to modify graphene oxide. The amount of phthalic anhydride used directly affects the modification effect. The present invention has no special limitation on the source of the phthalic anhydride, and commercially available products known to those skilled in the art can be used.

[0037] Based on 1 part by weight of GO, the raw materials for preparing the modified GO solution include 60 to 63 parts of acetone, preferably 60 to 62 parts, and more preferably 60 to 61 parts. In the present invention, the acetone is used to remove excess phthalic anhydride (PA). The amount of acetone directly affects the purity of the product. The present invention has no special limitation on the source of the acetone, and commercially available products known to those skilled in the art can be used.

[0038] Based on 1 part by weight of GO, the raw materials for preparing the modified GO solution include 90 to 93 parts of deionized water, preferably 90 to 92 parts, and more preferably 90 to 91 parts. In the present invention, the deionized water is used to dilute and dissolve the solution produced during the modification process. The amount of deionized water directly affects the concentration of the modified GO solution. The present invention has no special limitation on the source of the deionized water, and commercially available products known to those skilled in the art can be used.

[0039] Based on 1 part by weight of GO, the raw materials for preparing the modified GO solution include 90 to 94 parts of anhydrous ethanol, preferably 90 to 93 parts, and more preferably 90 to 92 parts. In the present invention, the anhydrous ethanol is used for repeated washing and final dissolution of the product. The amount of anhydrous ethanol directly affects the purity of the product and the cleanliness of the modified GO solution finally obtained. The present invention has no special limitation on the source of the anhydrous ethanol, and commercially available products known to those skilled in the art can be used.

[0040] Specifically, the mixing of GO and N-methylpyrrolidone (NMP) with phthalic anhydride (PA) is preferably first dispersed by an ultrasonic disperser, and the frequency of the disperser is preferably 3HZ; the dispersion time is preferably 50min to 1h, and more preferably 1h. In the present invention, after GO and N-methylpyrrolidone (NMP) are blended, they are placed in a three-necked flask with mechanical stirring and condensation reflux protection and mixed with phthalic anhydride. In the present invention, when phthalic anhydride is just added, the reaction temperature is preferably about 63 to 65°C, and after the phthalic anhydride is completely melted, the reaction temperature is preferably 83 to 85°C. The reaction time is preferably 1h. In the present invention, the standing time after the reaction is preferably 2h. In the present invention, for filtration, the filtration technical solution familiar to personnel can be adopted, and the number of filtrations in the present invention is preferably 3 times. In the present invention, the vacuum drying is preferably a vacuum oven, and the temperature is preferably set to 45 to 50°C. The drying time is preferably 6 hours to ensure that the product is completely dried to maintain its stability and quality. The vacuum degree is preferably 75-100 mbar to ensure effective removal of the solvent while avoiding excessive vacuum that affects equipment and operational safety.

[0041] The modified SiCnw preparation method is as follows: dispersing SiCnw into an L-lysine solution, stirring and centrifuging, washing with anhydrous ethanol and vacuum drying to obtain modified positively charged SiCnw. The raw materials required for preparing the modified SiCnw are calculated by weight as follows: 1 to 3 parts of SiCnw, 148 to 152 parts of L-lysine, 200 to 202 parts of deionized water, and 199 to 201 parts of anhydrous ethanol.

[0042] In terms of weight, the raw material of the modified SiCnw includes 1 to 3 parts of SiCnw, preferably 1 to 2 parts, and more preferably 1 part. In the present invention, the SiCnw is the original silicon carbide nanowire before modification, which is mainly used to react with the L-lysine solution to achieve modification. The amount of SiCnw affects the modification effect and the performance of the modified material. The present invention has no special limitation on the source of the SiCnw, and commercially available products known to those skilled in the art can be used.

[0043] Based on 1 part by weight of SiCnw, the raw materials for preparing the modified SiCnw include 148 to 152 parts of L-lysine, preferably 149 to 151 parts. In the invention, the L-lysine is used to react with SiCnw to bring about a modified SiCnw with a positive charge. The amount of L-lysine used directly affects the introduction of charge and the modification effect during the modification process. The present invention has no special limitation on the source of the L-lysine, and commercially available products known to those skilled in the art can be used.

[0044] Based on 1 part by weight of SiCnw, the raw materials for preparing the modified SiCnw include 200 to 203 parts of deionized water, preferably 200 to 202 parts, and more preferably 200 to 201 parts. In the present invention, deionized water is used to dissolve L-lysine and disperse SiCnw. The amount of deionized water affects the uniformity of dispersion and the efficiency of the modification reaction. The present invention does not specifically limit the source of the deionized water, and commercially available products known to those skilled in the art can be used.

[0045] Based on 1 part by weight of SiCnw, the raw materials for preparing the modified SiCnw include 199 to 201 parts of anhydrous ethanol, preferably 199 to 200 parts, and more preferably 200 parts. In the present invention, anhydrous ethanol is used to wash the modified SiCnw, remove unreacted substances and ensure the purity of the final product. The amount of anhydrous ethanol affects the washing effect and the quality of the modified SiCnw. The present invention has no special limitation on the source of the anhydrous ethanol, and commercially available products known to those skilled in the art can be used.

[0046] In the present invention, the preparation method of the modified SiCnw preferably comprises: dispersing SiCnw into an L-lysine solution, centrifuging after stirring, washing with anhydrous ethanol and then vacuum drying to obtain modified positively charged SiCnw. The L-lysine solution is L-lysine dissolved in deionized water, and the pH is adjusted to 8-9. The mixing is preferably mechanical stirring. The stirring rate is preferably 50-200rpm, more preferably 150-200rpm; the stirring time is preferably 30min-1h, more preferably 1h. The centrifuge is preferably a desktop high-speed centrifuge, the centrifugal speed is preferably 13000-15000rpm, and the centrifugal time is preferably 10-15 minutes. The vacuum drying temperature is preferably set to 25-30°C. The drying time is preferably 1 hour to ensure that the product is thoroughly dried to maintain its stability and quality. The vacuum degree is preferably 75-100mbar to ensure effective removal of the solvent while avoiding excessive vacuum degree affecting equipment and operation safety.

[0047] The modified CNTs preparation method is as follows: CNTs are added to deionized water and ultrasonically dispersed. After the CNTs are uniformly dispersed, they are coated on a glassy carbon electrode, and after drying, a uniform CNTs thin layer is formed on the glassy carbon electrode; sodium acetate and boric acid are added to the electrolytic cell to form an electrolyte; then, one end of the working electrode, the counter electrode and the reference electrode are inserted into the electrolyte, and the other end is connected to the electrochemical workstation, and a multi-step voltage program is applied for electrochemical oxidation treatment. After the reaction is completed, the working electrode is taken out, fully washed with deionized water, and then dried in a vacuum drying oven at 58 to 60°C for several hours to ensure that the surface of the CNTs is clean. Finally, the modified CNTs powder is obtained by physical stripping. Among them, the raw materials required for making modified CNTs are calculated by weight: 1 to 1.3 parts of CNTs, 10 to 13 parts of sodium acetate, 23 to 28 parts of boric acid, and 103 to 108 deionized water.

[0048] In terms of weight, the raw material of the modified CNTs includes 1 to 1.3 parts of CNTs, preferably 1 to 1.2 parts, and more preferably 1 part. In the present invention, the CNTs are mainly coated on the glassy carbon electrode as a modified component to generate hydroxyl groups on its surface by an electrochemical oxidation method. The amount of CNTs used affects the modification effect and the performance of the modified material. The present invention does not specifically limit the source of the CNTs, and commercially available products known to those skilled in the art can be used.

[0049] Based on 1 part by weight of CNTs, the raw material for preparing the modified CNTs includes 103-108 parts of deionized water, preferably 103-106 parts, and more preferably 102-104 parts. Deionized water is used to evenly disperse the CNTs so as to form a uniform thin layer on the surface of the glassy carbon electrode. There is no particular restriction on the source of deionized water, and commercially available experimental grade deionized water can be used.

[0050] Based on 1 part by weight of CNTs, the raw materials for preparing the modified CNTs include 10 to 13 parts of sodium acetate, preferably 10 to 12 parts, and more preferably 11 to 12 parts. Sodium acetate is used to mix with boric acid to form an electrolyte, and the pH value of the electrolyte is controlled between 5 and 6 to ensure that the electrochemical oxidation process is mild and uniform. The sodium acetate used can use a commercially available high-purity product.

[0051] Based on 1 part by weight of CNTs, the raw materials for preparing the modified CNTs include 23 to 28 parts of boric acid, preferably 23 to 26 parts, and more preferably 23 to 25 parts. Boric acid is used to mix with sodium acetate to form an electrolyte, and the pH value of the electrolyte is controlled between 5 and 6 to ensure that the electrochemical oxidation process is mild and uniform. The boric acid used can use a commercially available high-purity product.

[0052] In the specific process of preparing modified CNTs, the ultrasonic dispersion is dispersed by an ultrasonic disperser, and the frequency of the disperser is preferably 3Hz; the dispersion time is preferably 50min to 1h, and more preferably 1h. The vacuum drying temperature after coating the CNTs is preferably set to 32 to 38°C. The drying time is preferably 12 hours to ensure that the product is thoroughly dried to maintain its stability and quality. The concentrations of the sodium acetate solution and the boric acid solution are both selected to be 0.05M. The working electrode is a glassy carbon electrode coated with CNTs, the counter electrode is a platinum electrode, and the reference electrode is a silver / silver chloride electrode. The multi-step voltage program is divided into three steps: the first step is to apply a constant potential of 0.7V to 0.8V for 10 to 13 minutes to gently introduce hydroxyl groups to avoid excessive oxidation. The second step: apply a constant potential of 1.0 to 1.1V for 5 to 8 minutes to enhance surface oxidation. The third step of voltage treatment: apply a constant potential of 0.5 to 0.6V for 4 to 5 minutes to perform stabilization treatment to ensure uniform distribution of functional groups. After the electrochemical oxidation is completed, the vacuum drying temperature is preferably set to 58-60° C., and the drying time is preferably 3 hours. The physical stripping method is to use a special spatula to gently strip the modified CNTs film from the edge of the glassy carbon electrode.

[0053] The specific steps of the preparation method of the infrared stealth hybrid Mxene aerogel are:

[0054] (1) Modified SiCnw powder, modified GO solution, and modified CNTs were ultrasonically mixed and then added to TI 3 C 2 T X The Mxene solution was heated in a water bath under an argon atmosphere and stirred to mix, and then I-ascorbic acid (VC) was added and continued to stir, and then cooled in an ice bath to obtain a hybrid Mxene hydrosol.

[0055] Specifically, the modified SiCnw powder, modified GO solution and modified CNTs are preferably dispersed by an ultrasonic disperser, and the frequency of the disperser is preferably 3 Hz; the dispersion time is 50 min to 1 h, preferably 1 h.

[0056] After the raw materials are mixed, the Mxene solution is added and stirred in a water bath under an argon atmosphere. The argon atmosphere of the present invention is preferably a closed argon space with a pressure of 1 atm. The hydrothermal mixing is preferably firstly hydrothermally mixed at 58-60°C under autogenous pressure for 3-4 hours, and then hydrothermally mixed at 70°C under autogenous pressure for 1-2 hours. The stirring is preferably mechanical stirring. The stirring rate is preferably 50-200 rpm, more preferably 150-200 rpm.

[0057] After being mixed evenly, I-ascorbic acid (VC) is added dropwise to the solution and stirring is continued for 45 min to 1 h. In terms of mass ratio, the mass ratio of the MXene solution of the present invention to VC is 1:0.2 to 0.4, and is more preferably 1:0.3 to 0.4. The stirring is preferably mechanical stirring. The stirring rate is preferably 50 to 200 rpm, and more preferably 150 to 200 rpm. The present invention has no special limitation on the source of the VC, and commercially available products known to those skilled in the art can be used.

[0058] After the reaction is complete, the hybrid Mxene hydrosol is obtained by cooling in an ice bath, wherein the ice bath temperature is preferably -2°C to -1°C, and the cooling time is preferably 2h.

[0059] (2) Solvent replacement is performed on the hybrid Mxene hydrosol, and freeze-drying is performed to obtain a hybrid Mxene aerogel.

[0060] Specifically, after obtaining the Mxene hydrosol, the present invention preferably immerses the hydrosol in an ethanol solution and allows the solution to stand for solvent replacement. In the present invention, the replacement time is preferably 24 to 32 hours; the replacement time is preferably 30 hours.

[0061] After solvent replacement, the ethanol solution in the sol is evaporated by freeze drying to obtain hybrid Mxene aerogel. In the present invention, the freeze drying method uses a freeze dryer, the freezing temperature is set to -20 to -30°C, the freezing time is 48 hours, and the pressure is selected to be a vacuum-like environment below 10Pa.

[0062] (3) The hybrid MXene aerogel is annealed at 600-610°C under argon conditions to obtain an infrared stealth hybrid MXene aerogel doped with modified SiCnw, modified CNTs, and modified RGO.

[0063] Specifically, after the aerogel is formed, the aerogel is annealed under argon conditions to remove excess VC, thereby obtaining the desired infrared stealth hybrid MXene aerogel. In the present invention, the annealing conditions are annealing at 1 atm, 600-610° C. argon conditions for 55-60 min, and pressing at 5-5.2 MPa pressure for 5-6 min.

[0064] The present invention is provided by TI 3 C 2 T X TI in Mxene solution 3 C 2 T XMxene materials improve the low infrared emission characteristics of aerogels, which can reduce the difference in infrared radiation between aerogel smoke screens and the surrounding environment; by adding modified GO, the mid- and far-infrared extinction performance of aerogel smoke screens is improved, and the agglomeration of GO particles when mixed with other substances is reduced by modification; by adding VC as a reducing agent to modify the surface functional groups of MXene, MXene oxidation is hindered, and the modified GO is reduced to modified RGO; by adding modified CNTs as a cross-linking agent, the rich hydroxyl groups on the surface of modified CNTs are used to help the oxygen-containing functional groups on the surface of MXene and the modified RGO to combine through hydrogen bond interactions, thereby improving the comprehensive infrared stealth performance of aerogels and improving the weak gelation phenomenon of Mxene. By introducing modified SiCnw, the mechanical strength of the gel is improved, and the gel heat dissipation is uniform.

[0065] The method for preparing the infrared stealth hybrid MXene aerogel provided by the present invention is simple to operate and ensures the infrared stealth performance.

[0066] The present invention also provides the application of the infrared stealth hybrid MXene aerogel described in the above technical solution or the infrared stealth hybrid MXene aerogel prepared by the preparation method in the field of infrared stealth. In the present invention, the infrared stealth hybrid MXene aerogel is added to the stealth smoke forming agent to play the role of infrared stealth.

[0067] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0068] Example 1

[0069] TI 3 C 2 T X The mass ratio of Mxene solution, modified SiCnw powder, modified GO solution, modified CNTs, and VC is 1:0.4:2.2:0.8:0.3.

[0070] TI by weight 3 C 2 T X Mxene solution raw material: TI 3 ALC 2 3 parts, 9M hydrochloric acid solution 61 parts, LIF 3 parts, deionized water 75 parts.

[0071] TI 3 C 2 T X Preparation of Mxene solution: 3 g TI was added at 25 °C. 3 ALC 2Add to 60ml hydrochloric acid solution containing 3g LIF and mechanically stir and mix at 150rpm for 45min. After complete reaction, centrifuge at 13000rpm in a desktop high-speed centrifuge, collect the precipitate after 15 minutes; add hydrochloric acid to the precipitate, centrifuge to remove excess unreacted LIF, centrifuge steps are the same as above; rinse with deionized water until the pH is about 7, centrifuge to collect the precipitate, centrifuge steps are the same as above; add deionized water to the precipitate, and perform ice water bath ultrasonic treatment for 2h at 25kHz frequency, -2℃ temperature, 50W power, centrifuge to collect the upper solution, and obtain TI 3 C 2 T X For the Mxene solution, the centrifugation steps are the same as above.

[0072] The modified SiCnw powder raw materials are calculated by weight as follows: 1 part of SiCnw, 151 parts of L-lysine, 200 parts of deionized water, and 200 parts of anhydrous ethanol.

[0073] Preparation of modified SiCnw: 3 g SiCnw was dispersed in 453 ml of L-lysine solution at 25 °C, mechanically stirred at 150 rpm for 1 h, then centrifuged at 13,000 rpm for 15 min in a desktop high-speed centrifuge, washed with anhydrous ethanol, and vacuum dried in a vacuum dryer at 30 °C and 100 mbar for 1 h to obtain modified positively charged SiCnw.

[0074] The raw materials of the modified GO solution are calculated by weight as follows: 1 part of GO, 100 parts of N-methylpyrrolidone, 30 parts of phthalic anhydride, 60 parts of acetone, 90 parts of deionized water, and 90 parts of anhydrous ethanol.

[0075] Preparation of modified GO solution: 0.5g GO and 50ml N-methylpyrrolidone were mixed in a beaker, and ultrasonic dispersion was performed at 3HZ frequency for 1h using an ultrasonic disperser. The treated product was placed in a three-necked flask with mechanical stirring and condensation reflux protection, and 15g phthalic anhydride was added and the temperature was raised to 63°C for reaction; after the solid was completely melted, the temperature was raised to 85°C for further reaction for 1h, and an appropriate amount of acetone was added to remove excess phthalic anhydride, and the mixture was allowed to stand for 2h. When a large amount of black flocculent precipitate was observed, it was filtered 3 times to remove impurities, and the product was repeatedly washed with anhydrous ethanol and dried in a vacuum oven at 50°C and 100mbar for 6h to obtain phthalic anhydride grafted graphene oxide. The modified GO and deionized water were ultrasonically mixed at 3HZ frequency and 27°C for 1h using an ultrasonic mixer to finally obtain a modified GO solution.

[0076] The modified CNTs powder raw materials are calculated by weight as follows: 1 part of CNTs, 23 parts of 0.05M boric acid, 11 parts of 0.05M sodium acetate, and 103 parts of deionized water.

[0077] Preparation of modified CNTs powder: 5g CNTs were added to 515ml deionized water and ultrasonically dispersed at 3HZ frequency for 1h using an ultrasonic disperser. After the CNTs were evenly dispersed, they were coated on a glassy carbon electrode and placed in a vacuum drying oven at 35°C for 12h to form a uniform CNTs thin layer on the glassy carbon electrode; 500ml sodium acetate and 1045ml boric acid were added to the electrolytic cell to form an electrolyte; then, one end of the CNTs-coated glassy carbon electrode, platinum electrode and silver / silver chloride electrode was inserted into the electrolyte, and the other end was connected to the electrochemical workstation, and three potentials were applied respectively. The first time, a constant potential of 0.8V was applied for 10 minutes. The second time, a constant potential of 1.1V was applied for 5 minutes. The third step applied a constant potential of 0.6V for 4 minutes. After the reaction was completed, the working electrode was taken out, fully washed with deionized water, and then placed in a vacuum drying oven at 58-60°C for 3 hours to ensure that the CNTs surface was clean. Finally, a special spatula was used to gently peel off the modified CNTs film from the edge of the glassy carbon electrode.

[0078] Preparation of hybrid aerogel: Modified SiCnw powder, modified GO solution, and modified CNTs were ultrasonically dispersed at 3 Hz for 1 h and then added to TI 3 C 2 T X The MXene solution was then hydrothermally mixed at 58°C for 3h in a closed argon atmosphere at a pressure of 1atm, and then hydrothermally mixed at 70°C for 1h. During the mixing process, mechanical stirring was performed at a rate of 150rpm. After uniform mixing, I-ascorbic acid (VC) was dropped into the solution and mechanical stirring was continued at a rate of 150rpm for 45min. After the reaction was complete, the MXene hydrosol was cooled in an ice bath at -1°C for 2h to obtain the MXene hydrosol, which was immersed in an ethanol solution and allowed to stand for 30h for solvent replacement. After the replacement, a freeze dryer was used to freeze for 48h at -20°C and a vacuum environment with a pressure lower than 10Pa, and the ethanol solution was evaporated to form an aerogel. Finally, the aerogel was annealed at 1atm, 600°C, and an argon atmosphere for 60min, and then pressed at a pressure of 5MPa for 5min to remove VC in the hybrid gel to obtain an infrared stealth hybrid MXene aerogel doped with modified silicon carbide nanowires, modified carbon nanotubes, and modified reduced graphene oxide.

[0079] Example 2

[0080] TI 3 C 2 T X The mass ratio of Mxene solution; modified SiCnw powder; modified GO solution; modified CNTs; VC is 1:0.5:2.2:0.7:0.3.

[0081] TI 3 C 2 T X The raw materials of Mxene solution are calculated by weight: TI 3 ALC 2 4 parts, 8M hydrochloric acid solution 60 parts, LIF 3 parts, deionized water 77 parts.

[0082] TI 3 C 2 T X Preparation of Mxene solution: 4 g TI was added at 23 °C. 3 ALC 2 Add to 60ml hydrochloric acid solution containing 4g LIF and mechanically stir at 170rpm for 1h. After complete reaction, centrifuge at 14000rpm in a desktop high-speed centrifuge, collect the precipitate after 13 minutes; add hydrochloric acid to the precipitate, centrifuge to remove excess unreacted LIF, centrifuge steps are the same as above; rinse with deionized water until the pH is about 7, centrifuge to collect the precipitate, centrifuge steps are the same as above; add deionized water to the precipitate, and perform ice water bath ultrasonic treatment at 30kHz frequency, -1℃ temperature, 60W power for 2h, centrifuge to collect the upper solution, and obtain TI 3 C 2 T X For the Mxene solution, the centrifugation steps are the same as above.

[0083] The modified SiCnw powder raw materials are calculated by weight as follows: 1 part of SiCnw, 149 parts of L-lysine, 201 parts of deionized water, and 200 parts of anhydrous ethanol.

[0084] Preparation of modified SiCnw: 3g SiCnw was dispersed in 447ml L-lysine solution at 25°C, mechanically stirred at 170rpm for 45min, then centrifuged at 14000rpm for 20min in a desktop high-speed centrifuge, washed with anhydrous ethanol, and vacuum dried in a vacuum dryer at 28°C and 75mbar for 1h to obtain modified positively charged SiCnw.

[0085] The raw materials of the modified GO solution are calculated by weight as follows: 1 part of GO, 102 parts of N-methylpyrrolidone, 32 parts of phthalic anhydride, 61 parts of acetone, 90 parts of deionized water, and 91 parts of anhydrous ethanol.

[0086] Preparation of modified GO solution: 0.5g GO and 51ml N-methylpyrrolidone were mixed in a beaker, and ultrasonic dispersion was performed at 3HZ frequency for 1h using an ultrasonic disperser. The treated product was placed in a three-necked flask with mechanical stirring and condensation reflux protection, and 16g phthalic anhydride was added and the temperature was raised to 64°C for reaction; after the solid was completely melted, the temperature was raised to 83°C and the reaction was continued for 1h, and an appropriate amount of acetone was added to remove excess phthalic anhydride, and the mixture was allowed to stand for 2h. When a large amount of black flocculent precipitate was observed, it was filtered 3 times to remove impurities, and the product was repeatedly washed with anhydrous ethanol and dried in a vacuum oven at 47°C and 90mbar for 6h to obtain phthalic anhydride grafted graphene oxide. The modified GO and deionized water were ultrasonically mixed at 3HZ frequency and 27°C for 1h using an ultrasonic mixer to finally obtain a modified GO solution.

[0087] The modified CNTs powder raw materials are calculated by weight as follows: 1 part of CNTs, 24 parts of 0.05M boric acid, 12 parts of 0.05M sodium acetate, and 104 parts of deionized water.

[0088] Preparation of modified CNTs powder: 5g CNTs were added to 520ml deionized water and ultrasonically dispersed at 3HZ frequency for 1h using an ultrasonic disperser. After the CNTs were evenly dispersed, they were coated on a glassy carbon electrode and placed in a vacuum drying oven at 35°C for 12h to form a uniform CNTs thin layer on the glassy carbon electrode; 500ml sodium acetate and 1000ml boric acid were added to the electrolytic cell to form an electrolyte; then, one end of the CNTs-coated glassy carbon electrode, platinum electrode and silver / silver chloride electrode was inserted into the electrolyte, and the other end was connected to the electrochemical workstation, and three potentials were applied respectively. The first time, a constant potential of 0.8V was applied for 12 minutes. The second time, a constant potential of 1.1V was applied for 6 minutes. The third step applied a constant potential of 0.6V for 5 minutes. After the reaction was completed, the working electrode was taken out, fully washed with deionized water, and then placed in a vacuum drying oven at 58-60°C for 3 hours to ensure that the CNTs surface was clean. Finally, a special spatula was used to gently peel off the modified CNTs film from the edge of the glassy carbon electrode.

[0089] Preparation of hybrid aerogel: Modified SiCnw powder, modified GO solution and modified CNTs were ultrasonically dispersed at 3 Hz for 1 h and then added with TI 3 C 2 T XThe MXene solution was then hydrothermally mixed at 60°C for 4 hours in a closed argon atmosphere at a pressure of 1 atm, and then hydrothermally mixed at 70°C for 2 hours. During the mixing process, mechanical stirring was performed at a rate of 200 rpm. After the mixture was uniformly mixed, I-ascorbic acid (VC) was dropped into the solution and mechanical stirring was continued at a rate of 200 rpm for 45 minutes. After the reaction was complete, the MXene hydrosol was cooled in an ice bath at -2°C for 2 hours to obtain the MXene hydrosol, which was immersed in an ethanol solution and allowed to stand for 25 hours for solvent replacement. After the replacement, a freeze dryer was used to freeze the solution at -25°C and a vacuum environment with a pressure lower than 10 Pa for 48 hours to evaporate the ethanol solution to form an aerogel. Finally, the aerogel was annealed at 1 atm, 600°C, and an argon atmosphere for 60 minutes, and then pressed at a pressure of 5.2 MPa for 6 minutes to remove VC in the hybrid gel to obtain an infrared stealth hybrid MXene aerogel doped with modified silicon carbide nanowires, modified carbon nanotubes, and modified reduced graphene oxide.

[0090] Example 3

[0091] TI 3 C 2 T X The mass ratio of Mxene solution; modified SiCnw powder; modified GO solution; modified CNTs; VC is 1:0.5:2.3:0.6:0.4.

[0092] TI 3 C 2 T X The raw materials of Mxene solution are calculated by weight: TI 3 ALC 2 3 parts, 9M hydrochloric acid solution 61 parts, LIF 4 parts, deionized water 76 parts.

[0093] TI 3 C 2 T X Preparation of Mxene solution: 3 g TI was added at 24 °C. 3 ALC 2 Add to 61ml hydrochloric acid solution containing 4g LIF and mechanically stir at 200rpm for 50min. After complete reaction, centrifuge at 13000rpm using a desktop high-speed centrifuge, collect the precipitate after 20 minutes; add hydrochloric acid to the precipitate, centrifuge to remove excess unreacted LIF, centrifuge steps are the same as above; rinse with deionized water until the pH is about 7, centrifuge to collect the precipitate, centrifuge steps are the same as above; add deionized water to the precipitate, and perform ice water bath ultrasonic treatment for 2h at 27kHz frequency, -2℃ temperature, 80W power, centrifuge to collect the upper solution, and obtain TI 3 C 2 T XFor the Mxene solution, the centrifugation steps are the same as above.

[0094] The modified SiCnw powder raw materials are calculated by weight as follows: 1 part of SiCnw, 150 parts of L-lysine solution, 200 parts of deionized water, and 200 parts of anhydrous ethanol.

[0095] Preparation of modified SiCnw: 3g SiCnw was dispersed in 450ml L-lysine solution at 25°C, mechanically stirred at 200rpm for 1h, then centrifuged at 15000rpm for 17min in a desktop high-speed centrifuge, washed with anhydrous ethanol, and vacuum dried in a vacuum dryer at 30°C and 80mbar for 1h to obtain modified positively charged SiCnw.

[0096] The raw materials of the modified GO solution are calculated by weight as follows: 1 part of GO, 101 parts of N-methylpyrrolidone, 31 parts of phthalic anhydride, 60 parts of acetone, 90 parts of deionized water, and 90 parts of anhydrous ethanol.

[0097] Preparation of modified GO solution: 0.5g GO and 50.5ml N-methylpyrrolidone were mixed in a beaker, and ultrasonic dispersion was performed at 3HZ frequency for 1h using an ultrasonic disperser. The treated product was placed in a three-necked flask with mechanical stirring and condensation reflux protection, and 15.5g phthalic anhydride was added and the temperature was raised to 65°C for reaction; after the solid was completely melted, the temperature was raised to 84°C for further reaction for 1h, and an appropriate amount of acetone was added to remove excess phthalic anhydride, and the mixture was allowed to stand for 2h. When a large amount of black flocculent precipitate was observed, it was filtered 3 times to remove impurities, and the product was repeatedly washed with anhydrous ethanol and dried in a vacuum oven at 45°C and 100mbar for 6h to obtain phthalic anhydride grafted graphene oxide. The modified GO and deionized water were ultrasonically mixed at 3HZ frequency and 27°C for 1h using an ultrasonic mixer to finally obtain a modified GO solution.

[0098] The modified CNTs powder raw materials are calculated by weight as follows: 1 part of CNTs, 25 parts of 0.05M boric acid, 11 parts of 0.05M sodium acetate, and 104 parts of deionized water.

[0099] Preparation of modified CNTs powder: 5g CNTs were added to 520ml deionized water and ultrasonically dispersed at 3HZ frequency for 1h using an ultrasonic disperser. After the CNTs were evenly dispersed, they were coated on a glassy carbon electrode and placed in a vacuum drying oven at 35°C for 12h to form a uniform CNTs thin layer on the glassy carbon electrode; 500ml sodium acetate and 1136ml boric acid were added to the electrolytic cell to form an electrolyte; then, one end of the CNTs-coated glassy carbon electrode, platinum electrode and silver / silver chloride electrode was inserted into the electrolyte, and the other end was connected to the electrochemical workstation, and three potentials were applied respectively. The first time, a constant potential of 0.8V was applied for 13 minutes. The second time, a constant potential of 1.1V was applied for 7 minutes. The third step applied a constant potential of 0.6V for 4 minutes. After the reaction was completed, the working electrode was taken out, fully washed with deionized water, and then placed in a vacuum drying oven at 58-60°C for 3 hours to ensure that the CNTs surface was clean. Finally, a special spatula was used to gently peel off the modified CNTs film from the edge of the glassy carbon electrode.

[0100] Preparation of hybrid aerogel: Modified SiCnw powder, modified GO solution and modified CNTs were ultrasonically dispersed at 3 Hz for 1 h and then added with TI 3 C 2 T X The MXene solution was then hydrothermally mixed at 60°C for 3h in a closed argon atmosphere at a pressure of 1atm, and then hydrothermally mixed at 70°C for 2h. During the mixing process, mechanical stirring was performed at a rate of 170rpm. After uniform mixing, I-ascorbic acid (VC) was dropped into the solution and mechanical stirring was continued at a rate of 170rpm for 1h. After the reaction was complete, the MXene hydrosol was cooled in an ice bath at -1°C for 2h to obtain the MXene hydrosol, which was immersed in an ethanol solution and allowed to stand for 30h for solvent replacement. After the replacement, a freeze dryer was used to freeze for 48h at -30°C and a vacuum environment with a pressure lower than 10Pa, and the ethanol solution was evaporated to form an aerogel. Finally, the aerogel was annealed at 1atm, 600°C, and an argon atmosphere for 55, and then pressed at a pressure of 5.1MPa for 5min to remove VC in the hybrid gel to obtain an infrared stealth hybrid MXene aerogel doped with modified silicon carbide nanowires, modified carbon nanotubes, and modified reduced graphene oxide.

[0101] Table 1 Performance test results of hybrid aerogels prepared in Examples 1 to 3

[0102] Example 1 Example 2 Example 3 Near infrared band shielding rate 95% 92% 96% Short wavelength infrared band shielding rate 90% 93% 95% Mid-wavelength infrared band shielding rate 92% 91% 88% Visible light shielding rate 89% 86% 88%

[0103] It can be seen from the above embodiments that the infrared stealth aerogel provided by the present invention has a near-infrared band shielding rate of 96%, a short-wavelength infrared band shielding rate of 95%, a medium-wavelength infrared band shielding rate of 92%, and a visible light shielding rate of 89%.

[0104] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A method for preparing infrared stealth hybrid Mxene aerogel, characterized in that it comprises the following steps: (1) Preparation of TI3C2T X Mxene solution, modified silicon carbide nanowire (SiCnw) powder, modified GO solution, and modified carbon nanotubes (CNTs) were ultrasonically mixed and then added to TI3C2T X The Mxene solution was heated in a water bath under an argon atmosphere and stirred to mix, and then I-ascorbic acid (VC) was added and continued to stir, and then cooled in an ice bath to obtain a hybrid Mxene hydrosol; The modified silicon carbide nanowire (SiCnw) powder is SiCnw modified with cations and carrying positive charges; The modified reduced graphene oxide (RGO) is modified graphene oxide PA-GO modified by phthalic anhydride (PA) and having carboxyl groups on the surface; The modified CNTs are modified carbon nanotubes with hydroxyl groups on the surface; (2) performing solvent replacement on the hybrid Mxene hydrosol and freeze-drying to obtain a hybrid Mxene aerogel; (3) Annealing the aerogel at 600-610 °C under argon conditions to obtain the desired infrared stealth hybrid MXene aerogel.

2. The method for preparing infrared stealth hybrid MXene aerogel according to claim 1 is characterized in that, in the step (1), the mass ratio of MXene solution, modified SiCnw powder, modified GO solution, modified CNTs, and VC is 1: 0.3-0.5: 2-2.3: 0.6-0.8: 0.2-0.4, preferably 1: 0.4-0.5: 2.2-2.3: 0.7-0.8: 0.3-0.

4.

3. The method for preparing infrared stealth hybrid Mxene aerogel according to claim 1, characterized in that the TI3C2T X The preparation method of Mxene solution is as follows: TI3ALC2 is added to a hydrochloric acid solution containing LIF and stirred to mix; after the reaction is complete, the precipitate is collected by centrifugation; hydrochloric acid is added to the precipitate, and the excess unreacted LIF is removed by centrifugation; deionized water is rinsed until the pH reaches 6.5-7.5, and the precipitate is collected by centrifugation; deionized water is added to the precipitate, and ultrasonic treatment is performed in an ice water bath for 2 hours, and the upper layer solution is collected by centrifugation to obtain TI3C2T X Mxene solution; preferably, by weight, to make TI3C2T X The raw materials required for the Mxene solution are: 3 to 6 parts of TI3ALC2, 60 to 63 parts of hydrochloric acid solution, 3 to 7 parts of LIF, and 75 to 79 parts of deionized water; the selected hydrochloric acid concentration is 7 to 9M, preferably 8 to 9M.

4. The method for preparing infrared stealth hybrid MXene aerogel according to claim 1, characterized in that: The modified GO solution preparation method comprises: mixing GO with N-methylpyrrolidone (NMP) and then mixing with phthalic anhydride for modification, adding an appropriate amount of acetone to remove excess phthalic anhydride, and when a large amount of black flocculent precipitate is generated after standing, filtering to remove impurities, repeatedly washing the product with anhydrous ethanol and then vacuum drying to obtain phthalic anhydride grafted graphene oxide; ultrasonically mixing the modified GO with deionized water to obtain a modified GO solution; preferably, in parts by weight, the raw materials required for preparing the modified GO solution are: 1 to 3 parts of GO, 99 to 103 parts of N-methylpyrrolidone, 29 to 33 parts of phthalic anhydride, 60 to 63 parts of acetone, 90 to 93 parts of deionized water, and 90 to 94 parts of anhydrous ethanol; preferably, when phthalic anhydride is just added, the reaction temperature is preferably about 63 to 65° C., and after the phthalic anhydride is completely melted, the modification reaction temperature is preferably 83 to 85° C., and the reaction time is preferably 1 hour.

5. The method for preparing infrared stealth hybrid MXene aerogel according to claim 1, characterized in that: The modified SiCnw preparation method comprises: dispersing SiCnw into an L-lysine solution, stirring and centrifuging, washing with anhydrous ethanol and vacuum drying to obtain modified positively charged SiCnw; preferably, the raw materials required for preparing the modified SiCnw are, by weight, 1 to 3 parts of SiCnw, 148 to 152 parts of L-lysine, 200 to 202 parts of deionized water, and 199 to 201 parts of anhydrous ethanol.

6. The method for preparing infrared stealth hybrid MXene aerogel according to claim 1, characterized in that: The modified CNTs are prepared by electrochemical oxidation, and the steps are as follows: Add CNTs to deionized water and disperse them ultrasonically. After the CNTs are evenly dispersed, coat them on the glassy carbon electrode and form a uniform CNTs thin layer on the glassy carbon electrode after drying. Sodium acetate and boric acid are added to the electrolytic cell to form an electrolyte; then, one end of the working electrode, counter electrode and reference electrode is inserted into the electrolyte, and the other end is connected to the electrochemical workstation, and a multi-step voltage program is applied for electrochemical oxidation. After the reaction is completed, the working electrode is taken out, fully washed with deionized water, and then dried in a vacuum drying oven at 58-60°C for several hours to ensure that the surface of CNTs is clean, and finally the modified CNTs powder is obtained by physical stripping; preferably, the raw materials required for making modified CNTs are: 1-1.3 parts of CNTs, 10-13 parts of sodium acetate, 23-28 parts of boric acid, and 103-108 deionized water in parts by weight.

7. The method for preparing the infrared stealth hybrid MXene aerogel according to claim 4, characterized in that: In the preparation of modified CNTs, the multi-step voltage program in the electrochemical oxidation treatment includes: the first step, applying a constant potential of 0.7V to 0.8V for 10 to 13 minutes. The second step: applying a constant potential of 1.0 to 1.1V for 5 to 8 minutes. The third step of voltage treatment: applying a constant potential of 0.5 to 0.6V for 4 to 5 minutes. Preferably, the concentrations of the sodium acetate solution and the boric acid solution are both selected to be 0.05M.

8. The method for preparing infrared stealth hybrid MXene aerogel according to claim 1, characterized in that: The water bath heating stirring and mixing in step (1) is specifically as follows: first stirring and mixing in a water bath at 58-60° C. under autogenous pressure for 3-4 hours, and then mixing at 68-70° C. under autogenous pressure for 1-2 hours; preferably, the annealing conditions in step (3) are annealing at 1 atm, 600-610° C. under argon conditions for 55-60 minutes, and then pressing at 5-5.2 MPa pressure for 5-6 minutes to remove VC in the hybrid gel.

9. The infrared stealth hybrid MXene aerogel prepared by the preparation method according to any one of claims 1 to 8, characterized in that it is an infrared stealth hybrid MXene aerogel doped with modified silicon carbide nanowires (SiCnw), modified carbon nanotubes (CNTs) and modified reduced graphene oxide (RGO).

10. The use of the infrared stealth hybrid Mxene aerogel according to claim 9, characterized in that: As infrared stealth smoke screen matting agent, it is used to prepare infrared stealth smoke screen smoke forming agent.